(untitled) (World Economics and Finance Bulletin, 2022)
The division of the typical complementary product and the master into an additional product, the structural structure of the complementary product in farming and industry, the functional functions of the complementary product, as well as the necessary and complementary aspects of differentiation are all discussed in this article.